(untitled) (Journal of the College of Languages (JCL), 2024)
The paper deals with the language of Russian folklore. Folklore is a unique sphere of existence of the language, the most vivid expression of the national mentality. The folklore word embodied the perception and evaluation of the surrounding world. “What did the word in general mean for the life of the people? The word was equated ... with life itself. The word generated and explained life, it was ... the keeper of memory and the guarantee of the infinity of the future. The folklore text is studied by literary critics, ethnographers, historians, culturologists, and art historians. In the twentieth century, a new science emerged - linguo-folkloristics, the goals and objectives of which were formulated by A.T. Khrolenko only in the seventies. Some of the most frequently used words in folklore texts among other words such as "friend" were analyzed. It has been proven that some vocabulary spreads in one region over another, depending on the geographical and climatic environment. В работе рассматривается язык русского фольклора. Фольклор – это уникальная сфера существования языка, наиболее яркое выражение национальной ментальности. В фольклорном слове воплотились восприятие и оценка окружающего мира. «Что значило для народной жизни слово вообще? Слово приравнивалось… к самой жизни. Слово порождало и объясняло жизнь, оно было… хранителем памяти и залогом бесконечности будущего». Фольклорный текст исследуется литературоведами, этнографами, историками, культурологами, искусствоведами. В ХХ веке сложилась новая наука – лингвофольклористика, цели и задачи которой были сформулированы А.Т. Хроленко только в семидесятые годы. Received on 12/9/2023 Accepted on 2/11/2023 Published on 2/1/2024